2000
DOI: 10.1038/80310
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of transgenic elite commercial hybrid rice expressing Bacillus thuringiensis δ-endotoxin

Abstract: Here we describe development of transgenic elite rice lines expressing a Bt fusion gene derived from cryIA(b) and cryIA(c) under the control of rice actinI promoter. The lines used in the study were indica CMS restorer line of Minghui 63 and its derived hybrid rice Shanyou 63. The level of Bt fusion protein CryIA(b)/CryIA(c) detected in Minghui 63 (T51-1) plants was 20 ng/mg soluble protein. The Bt Shanyou 63 was field-tested in natural and repeated heavy manual infestation of two lepidopteran insects, leaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
258
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 411 publications
(274 citation statements)
references
References 21 publications
10
258
0
6
Order By: Relevance
“…The most commonly used Bt genes in transgenic crops including rice are Cry1Ab, Cry1Ac, and a fusion gene of Cry1Ac/Cry1Ab or Cry1Ab/c (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, binding tests of midgut brush border membrane vesicles showed that Cry1Aa, Cry1Ab, and Cry1Ac toxins share a common binding site (29)(30)(31); thus, a mutant that is able to overcome one of the Cry1A genes is also likely to be resistant to other Cry1A genes as well.…”
Section: Progresses In Gene Identification and Development Of Gsrmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used Bt genes in transgenic crops including rice are Cry1Ab, Cry1Ac, and a fusion gene of Cry1Ac/Cry1Ab or Cry1Ab/c (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). However, binding tests of midgut brush border membrane vesicles showed that Cry1Aa, Cry1Ab, and Cry1Ac toxins share a common binding site (29)(30)(31); thus, a mutant that is able to overcome one of the Cry1A genes is also likely to be resistant to other Cry1A genes as well.…”
Section: Progresses In Gene Identification and Development Of Gsrmentioning
confidence: 99%
“…2 A and B), the restorer line for a number of elite rice hybrids widely cultivated in China (28). Results from large-scale field tests in several provinces of China showed that this line and its hybrid with Zhenshan 97A, the male sterile line of the most popular hybrid Shanyou 63, were highly resistant to leaffolders and stemborers under field conditions, thus promising to significantly reduce insecticides, labor, and related costs while at the same time increase the yield and benefit the health of the farmers and consumers (33).…”
Section: Progresses In Gene Identification and Development Of Gsrmentioning
confidence: 99%
“…All the marker-free Ds(Bt) plants expressed the Bt protein at levels comparable with the positive control T51-1, a previously characterized Bt transgenic rice line (Tu et al, 2000).…”
Section: Analysis Of Transposition Activity In T1 Plantsmentioning
confidence: 99%
“…The use of genes encoding insecticidal proteins from Bacillus thuringiensis to confer resistance to various insect pests has been very successful in a number of crops (Moellenbeck et al ., 2001;Perlak et al ., 2001;Tu et al ., 2000). More recently, chitinase-encoding transgenes from certain fungi have been shown to improve plant defence against a broad range of fungal pathogens.…”
Section: Introductionmentioning
confidence: 99%